Sistematika dan Problematika Bimbingan Konseling di Perguruan Tinggi - Nurniswah Nurniswah (Institut Agama Islam Negeri Bengkulu, 2015)
Guidance and Counseling is very importance in college, because support to students in academic, attitude, and religion. Function of Guidance and Counseling services are distribution, fits, support, escalation, and defence. For maximal service in Guidance and Counseling, have to some condition like student use their mind, unperforce, leave bad habits, leave bad milieu, needs, ability by associate lecture, and believe by student, and prepared lecture. Student problems are study, family, identity ,rest time , mates, and himself, civil of campus, must be solve.